Overlap in the Disqualification Rules for Regional Head Election Winners - Ahmad Siboy; Benny Krestian Heriawanto; Retno Wulan Sekarsari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Regulations regarding the settlement of disputes in regional head elections are divided based on the types and qualifications of administrative violations, criminal administrative violations, electoral administrative disputes, criminal violations, outcome disputes, and ethical violations. The division of the qualifications of these problems has led to a settlement process that is not in harmony with each other. It even causes an overlapping process between one violation and another, between one judicial institution and another judicial institution, as in the case of the settlement of the cancellation of the winner of the regional head election in Bandar Lampung in 2020. This study investigates the issue of the rules for the cancellation of the candidate pair winning the regional head election. This study is normative juridical research. Furthermore, the research approach used is concept, legislation, and case approaches. The results of this study indicate that, based on the ius contituentum, the cancellation of the winner of the regional head election can be pursued through legal remedies for Criminal Administration Violations (Article 135A) which are tried by the Election Supervisory Body and Supreme Court. In addition, it can also be through the pathways of the Case of Dispute over Election Results (Article 156) which is tried by the Constitutional Court. The cancellation process by the two pathways has the potential to cause conflicting decisions on the same object, making it confusing at the execution stage.